Pelatihan Membaca Ekstensif Untuk Memperkuat Literasi Kelompok Ibu PKK BSD Dalam Memperoleh Informasi Yang Beragam di Era Digital - Riastri Novianita; Bobby Octavia Yuskar; Athiy dina rosihana; Ondy (Edujavare Publishing, 2025)
Literacy is the ability to read, write, and understand information in various contexts. Literacy can also be interpreted as the skill of processing information and knowledge for life skills. Literacy is a skill that needs to be trained and not a talent. Literacy has a very broad scope and is needed in everyday life. Types of literacy: Reading and writing literacy, Numeracy literacy, Science literacy, Digital literacy, Financial literacy, Cultural and civic literacy Benefits of literacy: Helping to access knowledge, Understanding lesson materials, Succeeding in the learning process, Cultivating students' character, Forming noble morals until adulthood, Helping to understand the rights and obligations of citizens, Helping to achieve financial well-being, Helping to participate in the environment, the surrounding community, In this modern era, the term